2018
DOI: 10.1186/s12935-018-0606-z
|View full text |Cite
|
Sign up to set email alerts
|

Clinicopathological and prognostic significance of long noncoding RNA MALAT1 in human cancers: a review and meta-analysis

Abstract: BackgroundThe aberrant regulation of MALAT1 has been indicated to be involved in various carcinogenic pathways contributing to the tumourigenesis and progression of cancers. The current meta-analysis summarized the research advances of MALAT1 functions and analyzed its prognostic value among multiple types of cancers.MethodsEligible studies were identified through retrieving the PubMed, Web of Science, and CNKI databases, up to Mar 1, 2018. 28 studies of 5436 patients and 36 studies of 3325 patients were enrol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
21
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 29 publications
(21 citation statements)
references
References 82 publications
0
21
0
Order By: Relevance
“…MALAT-1 has also been shown to induce epithelial-mesenchymal transition through the miR-204/ZEB2 axis in breast cancer [16]. A previous meta-analysis has shown that the up-regulation of MALAT-1 is significantly correlated with the prognosis and metastasis of cancers [17]. Nevertheless, the prognostic role of MALAT-1 in breast cancer is poorly characterized, with no systematic evaluation conducted to date [18,19].…”
Section: Introductionmentioning
confidence: 99%
“…MALAT-1 has also been shown to induce epithelial-mesenchymal transition through the miR-204/ZEB2 axis in breast cancer [16]. A previous meta-analysis has shown that the up-regulation of MALAT-1 is significantly correlated with the prognosis and metastasis of cancers [17]. Nevertheless, the prognostic role of MALAT-1 in breast cancer is poorly characterized, with no systematic evaluation conducted to date [18,19].…”
Section: Introductionmentioning
confidence: 99%
“…However, autophagy inhibition caused by increased MALAT1 has been rarely reported and investigated. For autophagy regulation, it is widely accepted that the mammalian target of rapamycin complex 1 (mTORC1) from the autophagy-inhibiting PI3k-Akt pathway [26] and increased MALAT1 could activate PI3K-AKT pathway in numerous cancers including GC [27]. In this study, we demonstrated that increased MALAT1 could inhibit autophagy ux through activating AKT/mTOR pathway.…”
Section: Discussionmentioning
confidence: 67%
“…MALAT1 overexpression was first described in cancer ( 76 ) and in response to 24 h hypoxic stimulus ( 77 , 78 ). However, there is increasing evidence that the direction of MALAT1 deregulation is dependent on the disease context ( 79 ) and recently MALAT1 was described to be downregulated in tissue samples from atherosclerotic coronary artery plaques ( 80 ). This is in line with our findings, were MALAT1 was downregulated in both primary and restenotic lesions.…”
Section: Discussionmentioning
confidence: 99%